KAJIAN KESESUAIAN PERLAKUAN AKUNTANSI MUDHARABAH DENGAN PSAK NO.105 PADA KOPERASI SYARIAH LAMONGAN - Eny Latifah; Soeparlan Pranoto; Endah Susilowati (Universitas Muhammadiyah Ponorogo, 2016)
The purpose of this study to determine the extent of accounting conformity of financing in KJKS BMT Bina Ummat Sejahtera Paciran Lamongan as the owner of the funds with SFAS No. 105. This research method with qualitative approach that is interpretive, where enterprise data is analyzed and compared with the concepts and theories to produce systems and methods of good decision making. Method of data validity using triangulation techniques. Research results mudharabah accounting treatment applied by KJKS can be said to be in accordance with SFAS 105, the suitability contained in the recognition, measurement and presentation, but in the disclosure of accounting is not appropriate because there is no disclosure of the allowance, and the recognition of gains is still calculated with projected results due to constraints financing members who are not able to present the books to the owner.